Trade Liberalization and Economic Growth: An Assessment of Nigerian Experience - Duru, Innocent .U.; Okafor, Bartholomew .O.N.; Adikwu, Friday .O.; Njoku, Franklin .C. (Asian Development Policy Review, 2020)
The association between trade liberalization and economic growth in Nigeria was examined in this study from 1981 to 2018. The study used the Autoregressive Distributed Lag Bounds technique to cointegration. The results showed that trade liberalization do not support economic growth in Nigeria. Hence, the genuineness of the extensive trade liberalization campaign in developing countries through the bright idea of international organizations in the late 1980s and early 1990s was not validated. Furthermore, the results showed the presence of unidirectional causality from real Gross Domestic Product to trade liberalization in Nigeria. The study, therefore, recommends that policymakers of the government should balance its strategies of trade liberalization as a result of the inability of the economy to absorb the adverse shocks from foreign trade, appropriate fiscal and monetary policies should be deployed by the government for the protection of the economy against foreign influences and the diversification of the structure of export is necessary to ensure that manufactured products are exported more. Also, the Central Bank of Nigeria and policymakers of the government should prescribe sound macroeconomic policies that will ensure price stability to reduce the uncertainties associated with investment in the economy to boost economic growth. The government should also provide incentives to investors and a conducive environment for investment. Moreover, the government should initiate policies of growth for the promotion of trade.